Optical tomography system: application of Charge Coupled Device (CCD) for solid and transparent objects detection - Jamaludin, J. (Penerbit UTM Press, 2016)
This research presents an application of Charge Coupled Device (CCD) linear sensor and laser diode in an optical tomography system. These optoelectronic sensors are believed to detect solid objects rather than transparent objects. Based on the research results, the development of optical tomography system using Charge Coupled Device (CCD) and laser diode has helped to enhance the potential of these sensors in detecting high to low opacity objects. Experiments for detecting a solid rod, glass rod and transparent hollow straw in non-flowing crystal clear water were conducted in this study. Investigation on the effect of number of views also studied in this research. From the image reconstruction results, it clearly shows a cross-sectional image of a pipeline system with the existence of opaque and transparent objects in multiphase flows. For 320 views image reconstruction, it gives high resolution of image results compared to 160 views image reconstruction.